PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN MEDIA KONKRET UNTUK MENINGKATAN PEMBELAJARAN MATEMATIKA TENTANG BANGUN RUANG PADA SISWA KELAS V SD NEGERI 2 LEMBUPURWO TAHUN AJARAN 2018/2019 - Sukoco, Arvrian; Rokhmaniyah, Rokhmaniyah; Joharman, Joharman (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
This study aims to improve mathematics learning outcomes about solid figures. This research is a collaborative Classroom Action Research (CAR) conducted in three cycles. The subjects are the teacher and the fifth grade students. Data collection techniques use observation, interviews, and tests. Data validity uses content validity, technical triangulation, and sources. Data analysis includes data reduction, data presentation, and drawing conclusions. The results indicates that the application of the Discovery Learning learning model can improve mathematics learning about solid figures in fifth grade students of SDN 2 Lembupurwo.